Entropy generation in radiative motion of tangent hyperbolic nanofluid in the presence of gyrotactic microorganisms and activation energy - Wu, Yong; Chaudhry, Munaza; Maqbool, Noureen; Tahir, Madeeha; Basit, Muhammad Abdul; Imran, Muhammad (Frontiers in Physics, 2024)
In this work, entropy generation is optimized through the application of the second law of thermodynamics. The slip mechanisms, Brownian diffusions as well as thermophoresis, are elaborated using the tangent hyperbolic nanomaterial model. MHD fluid is taken into consideration. To characterise the impact of activation energy, a unique model involving binary chemical reaction is deployed. The effects of mixed convection that is nonlinear in nature, bioconvection, and Joule effect are all taken into consideration. The key partial differential equations (PDEs) are reduced into ordinary differential equations (ODEs) by utilizing appropriate similarity transformations, and then solved numerically with the help of a built-in 'bvp4c' technique of MATLAB software. Varied flow parameters' impacts on the nanoparticle volume concentration, entropy number, microorganisms concentration, temperature, and velocity fields is analyzed using graphs. Various flow variables are taken into consideration to calculate the total rate of entropy generation. The obtained results show that concentration irreversibility, Joule effect irreversibility, viscous dissipation and heat irreversibility all influence entropy. The numerical outcomes observed by fixing the physical parameters as 0.1 4.0and there impact on the momentum, thermal, concentration, and microorganisms density profiles.From results, an increasing estimate of the variable representing chemical reaction indicates a decline in concentration. The higher the chemical reaction variable, Hartmann number, andWeissenberg number, the higher the entropy number, while the Bejan number has a contrary behaviour. Laterly all the outcomes are plotted in graphs and discussed in detail subject to the involving physical quantities.